Analysis of phlebotomy blood losses in neonates in a tertiary care hospital - Agrawal, Amit; Goyal, Shweta (Indian Journal of Child Health, 2017)
Introduction: Blood loss due to laboratory testing is greatest for the most premature neonates with very low birth weight who require many weeks of intensive support and monitoring. Objective: The purpose of this study was to find out the volume of blood withdrawn for analytical purposes in neonates. Design: Retrospective chart analysis Setting: Neonatal intensive care unit (NICU) of a tertiary care teaching hospital of central India Participants: Neonates admitted to NICU over a period of three months. All medical records of recruited patients were reviewed and amount of blood withdrawn for analytical purposes was recorded. Intervention: None Main Outcome Measures: The amount of blood overdrawn per test and blood overdrawn per newborn. Results: A total of 153 neonates were admitted to the NICU during the study period. A total of 684 samples were performed, corresponding to 4.47±3.36 (range 1-17) per neonate. The mean volume of blood removed was 9.38 ml ± 8.8 ml per newborn (range 1 -51 ml). The amount of blood withdrawn was inversely proportional to the gestational age and birth weight i.e., neonates less than 32 weeks gestation and those with birth weight